AgMgAl metallic glassy and intermetallic thin films for electric contact applications. (February 2015) - Lin, Y.T.; Chung, Y.L.; Wang, Z.K.; Huang, J.C.
Abstract: The AgMgAl thin films, in an attempt in replacing the expensive pure Au contact films, are prepared by co-sputtering. The surface morphology, roughness, amorphous or crystalline atomic structure, grain size, and electric resistivity are systematically examined. Depending on the film compositions, the films can be fully amorphous or fully nanocrystalline, or a composite with the mixture of nanocrystalline phases dispersed in the amorphous matrix. Under the as-sputtered condition, the crystalline group has the lowest resistivity, ranging from 27 to 37 μΩ·cm, the composite group lies in the middle, 31–70 μΩ·cm, and the fully amorphous group possesses the highest resistivity, 87–122 μΩ·cm. Appropriate short thermal annealing for the amorphous films can drastically lower the resistivity down to as low as 9 μΩ·cm, already compatible to pure Au (3–7 μΩ·cm). This study demonstrates the feasibility of the AgMgAl films in replacing the pure Au. Graphical abstract: Highlights: The electric resistivity of the Ag–Mg–Al sputtered thin films are systematically examined. The lowest electric resistivity achieved is 9 μΩ·cm, compatible to pure Au (3–7 μΩ·cm). The large single-phased AgMg crystalline grains is responsible for the low resistivity.